Healthcare worker attendance during the early stages of the COVID-19 pandemic: A longitudinal analysis of fingerprint-verified data from all public-sector secondary and tertiary care facilities in Bangladesh - Do, Duy; Sarker, Malabika; Chen, Simiao; Lenjani, Ali; Tikka, Pauli; Bärnighausen, Till; Geldsetzer, Pascal (Journal of Global Health, 2022)
This article was published in The Journal of Global Health [ © 2020 The Author(s) JoGH © 2020 ISGH] and the definite version is available at: https://doi.org/10.1101/2020.09.01.20186445 The Journal's website is at: https://jogh.org/documents/issue202002/jogh-10-020509.pdf